Evaluation of the Expenditures of Metropolitan Sub-Provincial Municipalities for Environmental Protection Services: The Case of the İzmir-Selçuk District Municipality - Dahi Zeynel Bakıcı (İzmir İktisat Dergisi, 2022)
The importance of environmental protection and control services, which have a significant place among municipal services, is gradually increasing today. Municipalities, which are among the administrations responsible for meeting local and common needs, constitute the administration of the locality where environmental problems are most intense. On the other hand, the fact that environmental problems observed in heavily industrialized and urbanized areas are intense causes these administrations to use more financial resources in fulfilling their environmental protection and control duties. The share and rate of environmental protection and control service expenditures in the budget expenditures of district municipalities within the municipal boundaries of the metropolitan municipalities, which are local administrative organizations, is the subject of our study. In this study, the ratio of environmental protection service expenditures, environmental protection, and control directorate expenditures, and environmental protection services and environmental protection and control directorate expenditures within the budget expenditures of İzmir-Selçuk District Municipality, according to the functional classification, which is a form of analytical budget classification, within the years 2014-2019 is analyzed by evaluating their ratio to the total municipality expenditures,. Along with literature and resource review, the study is an evaluation of the results of the ratio of the environmental protection expenditures and the expenditures of the environmental protection and control directorate, which are among the finalized budget items of the Selçuk District Municipality, which is on the UNESCO World Heritage List within the borders of İzmir Metropolitan Municipality, to the total budget figures between the years 2014-2019.